Effects of chromium yeast supplementation on productive and metabolic responses of laying hens fed diets containing different energy levels - Siloto, Estela Valeria [UNESP]; Sartori, Jose Roberto [UNESP]; Santos, Tatiane Souza dos [UNESP]; Fascina, Vitor Barbosa [UNESP]; Centenaro, Lucimara Patricia [UNESP]; Miranda, Carolina Carvalho de [UNESP]; Eigenheer Pinke Testa, Carolyne Assis [UNESP]; Silva Sartori, Denise Rangel da [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2021)
This study evaluated the effects of chromium yeast (Cr yeast) and two apparent metabolizable energy (AME) levels on productive performance, egg quality, and lipid and carbohydrate metabolism in laying hens. A total of 192 Bovans White laying hens at 47 weeks of age were randomly assigned to eight dietary treatments (six replicates each) in a 4 x 2 factorial arrangement: four levels of supplemental Cr (0, 0.2, 0.4, and 0.8 ppm as Cr yeast) and two AME levels (2,780 and 2,900 kcal AME kg(-1)). No significant effect of Cr yeast supplementation on feed intake, egg weight, egg production, intact eggs, egg mass, feed conversion ratio, or egg quality was observed. Egg quality parameters and Cr content in the yolk were not affected by dietary treatments. Plasma glucose and lipid levels were not influenced by either Cr yeast or AME levels used in this study. However, Cr yeast supplementation improved yolk percentage and hepatic glycogen content. The inclusion of Cr yeast at 0.2 and 0.4 ppm induced the highest hepatic glycogen content with the energy levels 2,900 and 2,780 kcal AME kg(-1), respectively. Laying hens fed 2,900 kcal AME kg(-1) showed the highest abdominal fat. The results observed in the present study support the hypothesis that the lack of positive effects of Cr yeast supplementation on production performance and egg quality may be related to good management practices, as the birds were not subjected to stressful conditions.
Keywords: egg quality; laying hen; lipid metabolism; mineral supplementation; serum parameters